2010
DOI: 10.1016/j.ijpsycho.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Timing is everything: Neural response dynamics during syllable processing and its relation to higher-order cognition in schizophrenia and healthy comparison subjects

Abstract: Successful linguistic processing requires efficient encoding of successively-occurring auditory input in a time-constrained manner, especially under noisy conditions. In this study we examined the early neural response dynamics to rapidly-presented successive syllables in schizophrenia participants and healthy comparison subjects, and investigated the effects of noise on these responses. We used magnetoencephalography (MEG) to reveal the time-course of stimulus-locked activity over bilateral auditory cortices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 76 publications
2
41
0
Order By: Relevance
“…Note however, that differences in delay duration used in human (hypothetical seconds to months) vs. animal (seconds to minutes) delay discounting tasks may limit cross-species translational validity of such testing (McClure et al, 2007;Schultz, 2010). Nevertheless, another important aspect of such decision-making paradigms concerns temporal perception (Wittmann et al, 2007), in that the ability to perceive time is often altered in patients with schizophrenia, bipolar disorder, and other conditions (McDowell et al, 1996;Dale et al, 2010;Papageorgiou et al, 2013) and can be affected by treatments such as amphetamine (Fowler et al, 2009). Such changes in temporal perception in patients should be taken into account in future studies investigating mechanistic changes underlying decision-making deficits.…”
Section: Other Methods For Assessing Flexible Decision-making Across mentioning
confidence: 99%
“…Note however, that differences in delay duration used in human (hypothetical seconds to months) vs. animal (seconds to minutes) delay discounting tasks may limit cross-species translational validity of such testing (McClure et al, 2007;Schultz, 2010). Nevertheless, another important aspect of such decision-making paradigms concerns temporal perception (Wittmann et al, 2007), in that the ability to perceive time is often altered in patients with schizophrenia, bipolar disorder, and other conditions (McDowell et al, 1996;Dale et al, 2010;Papageorgiou et al, 2013) and can be affected by treatments such as amphetamine (Fowler et al, 2009). Such changes in temporal perception in patients should be taken into account in future studies investigating mechanistic changes underlying decision-making deficits.…”
Section: Other Methods For Assessing Flexible Decision-making Across mentioning
confidence: 99%
“…Indeed, evidence from older adults shows that successful perceptual training induces more efficient and reliable prefrontal cortical operations, allowing for improved working memory performance (Berry et al, 2010;Gazzaley, 2010). Vinogradov et al have shown increases both in the amplitude of the M100 response in A1 and in very early g band oscillatory power in lateral prefrontal cortex after intensive auditory training in schizophrenia, concomitant with improved behavioral performance (Dale et al, 2010;Brown et al, under review). (3) Learning-induced plasticity is critically dependent on the behavioral state of the animal, and is profoundly influenced by neuromodulatory neurotransmitters.…”
Section: Wang Et Al 1995) Though We Do Not Yet Fully Understandmentioning
confidence: 99%
“…They applied 50 h of a research version of the software described above in the Mahncke et al study and compared it with 50 h of commercial computer games, examining behavioral outcomes as well as changes in serum biomarkers, MEG indices of early neural processing, and fMRI patterns of activation during untrained memory tasks (Adcock et al, 2009;Fisher et al, 2009Fisher et al, , 2010Dale et al, 2010;Hinckley et al, under review;Subramaniam et al, in press). Schizophrenia participants showed significant improvement in verbal learning and memory and in general cognition in response to training (effect sizes of 0.86 in a per protocol analysis); cognitive improvements were associated with improved quality of life at 6 months; subjects exposed to training showed significant increases in serum BDNF levels, while computer games control subjects did not; medication-induced serum anticholinergic activity was negatively correlated with the cognitive response to training; training increased restingstate a band functional connectivity in cortex; and also increased BOLD activation patterns in medial prefrontal cortex during an untrained memory task and restored the association between level of activation and task performance.…”
Section: Neuropsychopharmacology Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other study concluded there were no gains in neurocognition and no changes in electroencephalogram (EEG) measures following 40 hours of BrainFitness training [36]. Two other studies [37,38] that were published before our publication period showed improved verbal memory and auditory neural responses (M100) after intensive auditory training. The MEG findings contradict Rass et al's study [36], but are in line with the original neuroplasticity-based studies from Fisher and colleagues [34,39], which reported significant improvements in verbal learning and memory and global cognition, and maintenance of treatment gains at 6- month follow-up.…”
Section: Neuroplasticity-based Approachesmentioning
confidence: 97%